Overconfidence, CEO power e desempenho social corporativo - Costa, Ingrid Laís de Sena (2024)
The choice of corporate strategies that incorporate social and environmental aspects in organizational activity is a necessary point in current market configurations. Therefore, the decision-making process that encompasses these choices requires attention, mainly in relation to understanding the factors that affect it. Specifically, this research focuses on the behavioral attributes of managers that are related to decision making, such as overconfidence (OC) and the chief executive officer (CEO) power. Therefore, this study sought to analyze the influence of CEO power and overconfidence on corporate social performance (CSD). For this, the research sample included 180 non-financial publicly traded Brazilian companies, from 2010 to 2022, depending on data availability. The methodology had a quantitative-qualitative approach that included the composition of a DSC measure, defined based on a checklist of items related to institutional, social and environmental dimensions; the composition of measures of managerial overconfidence based on the CEO’s behavioral characteristics and organizational and remuneration characteristics; and a measure related to the CEO power, constructed observing Finkelstein’s four dimensions. Subsequently, these constructs were analyzed using descriptive and inferential statistics using multilinear regressions on panel data. The research results demonstrated that, with regard to corporate social performance, the companies investigated develop socio-responsive activities, but present an average adherence to the analyzed indicators, the result obtained was similar to the Refinitiv® ESG Score for the same period. The best-performing companies in the energy and sanitation sectors stood out. The evidence obtained suggests that the behavioral aspects of managers are related to the corporate social performance of Brazilian companies, in which overly confident managers positively affect the corporate social performance of companies. Regarding the CEO power structure, it was noticed that aspects related to expert and prestige power enhance the development of socio-responsible measures. Overall, it was found that the CEO power does not increase this manager’s overconfidence and, consequently, does not act as an effective moderating aspect of the relationship between overconfidence and corporate social performance. Furthermore, the findings contribute to the perspective discussed by theories of upper echelons, managerial power and agency, by providing evidence of the relationship between managers' behavior and the social performance of companies within an emerging scenario, as well as encompassing a pandemic period.